Composite heat-conducting, insulating and flame-retardant thermal interface material and preparation method thereof

By using BN-DTPMPA-Cu2+ filler and PET blended and extruded in thermal interface materials, the problems of low thermal conductivity and poor flame retardant properties of existing thermal interface materials are solved, and efficient thermal conductivity and flame retardant properties are achieved, which improves the application safety and breadth of materials.

CN119592023APending Publication Date: 2025-03-11GUIZHOU AEROSPACE TIANMA ELECTRICAL TECH

Patent Information

Application Number
CN202411684350.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The matrix organic polymers of existing thermal interface materials have low intrinsic thermal conductivity and poor flame retardant properties, limiting their application in high-density electronic devices.

Method used

By chelating boron nitride (BN) nanosheets with diethylenetriamine pentamethylenephosphonic acid (DTPMPA) and copper ions (Cu2+), BN-DTPMPA-Cu2+ filler was formed, and blended and extruded with polyethylene terephthalate (PET), PET/BN-DTPMPA-Cu2+ composite thermally conductive insulated flame retardant thermal interface material was prepared.

Benefits of technology

This material exhibits good thermal conductivity, flame retardant and mechanical properties in the fields of electronic devices and LED heat dissipation, which significantly improves the application safety and breadth of polymer materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592023A_ABST
    Figure CN119592023A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nano composite materials, in particular to a composite heat-conducting, insulating and flame-retardant thermal interface material and a preparation method thereof.The composite heat-conducting, insulating and flame-retardant thermal interface material is prepared from, by weight, 1-25% of BN-DTPMPA-Cu < 2 + > filler and 1-25% of polyethylene glycol terephthalate (PET) through blending extrusion, film forming and pressing, and the content of the BN-DTPMPA-Cu < 2 + > filler is 1-25%. The composite heat-conducting, insulating and flame-retardant thermal interface material has good application prospects in the heat dissipation fields of electronic devices, LEDs and the like, meanwhile, the PET / BN-DTPMPA-Cu < 2 + > composite heat-conducting, insulating and flame-retardant thermal interface material is good in environmental protection property and easy to prepare, and the application safety and universality of high polymer materials are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano composite materials, in particular to a composite thermally conductive, insulating, flame-retardant thermal interface material and a preparation method thereof. Background Art

[0002] At present, the integration density and power of electronic devices are getting higher and higher, which puts higher requirements on thermal interface materials. Usually, the matrix of thermal interface materials is organic polymers such as epoxy resin, polydimethylsiloxane, vinyl acetate copolymer, etc. These matrices have defects such as low intrinsic thermal conductivity and poor flame retardant properties. As we all know, polymer materials are materials based on polymer compounds. Polymer materials are materials composed of compounds with relatively high molecular weight, including rubber, plastic, fiber, coating, adhesive and polymer-based composite materials. Polymers are the form of life. Among them, polyethylene terephthalate, also known as polyester resin, has the greatest toughness among thermoplastics, good electrical insulation performance, good thermal stability, non-toxicity, weather resistance, good chemical resistance and low water absorption. However, the high flammability and low thermal conductivity of polymer materials greatly limit their application in these fields. Therefore, how to design and prepare thermal interface composite materials with high thermal conductivity and excellent flame retardant properties is crucial.

[0003] The two-dimensional layered materials widely studied at present usually include graphene, boron nitride, MXene, transition metal chalcogenides, black phosphorene, etc., which can be combined with polymer, ceramic or metal matrix to achieve breakthroughs in one direction or more performances on the basis of the original performance. Among them, boron nitride has excellent thermal conductivity, insulation and non-flammability. Due to its unique layered structure, it has a certain shielding effect and is widely used in the field of thermal conductive thermal interface materials. At present, DTPMPA-Cu 2+ The preparation of flame-retardant insulating thermal interface composites using chelates as flame retardants and catalysts has not been reported.

[0004] Therefore, finding a new preparation method that can improve the shortcomings of the original one-step method, such as high density and large-scale cracking, is the current key research direction. Summary of the invention

[0005] In order to solve the above technical problems existing in the prior art, the present invention provides a composite thermally conductive, insulating, flame-retardant thermal interface material and a preparation method thereof. Specifically, the present invention is achieved through the following technical solutions:

[0006] A method for preparing a composite thermally conductive, insulating, flame-retardant thermal interface material, characterized by comprising the following steps:

[0007] S1: placing a strong base and boron nitride BN powder into a stainless steel reactor, and causing a hydrothermal reaction in a closed environment with a pressure of more than 10 MPa and in water;

[0008] S2: subjecting the solution obtained in step S1 to ultrasonic centrifugation until it becomes neutral and collecting the boron nitride BN supernatant;

[0009] S3: prepare 21 μmol / L diethylenetriaminepentamethylenephosphonic acid;

[0010] S4: prepare 10-150 μmol / L anhydrous copper sulfate solution;

[0011] S5: DTPMPA was added to Cu 2+ Chelation was performed to obtain DTPMPA-Cu 2+ , measure a certain amount of DTPMPA-Cu 2+ Stir with boron nitride BN supernatant for 48 hours and then vacuum dry

[0012] S6: The filler dried in step S5 is mixed with polyethylene terephthalate (PET) in a certain proportion, and PET / BN-DTPMPA-Cu is prepared by co-extrusion. 2+ Composite thermally conductive, insulating and flame-retardant thermal interface material.

[0013] Furthermore, in step S1, the strong base is potassium hydroxide or sodium hydroxide, and the mass ratio of the strong base is 1:2-3.

[0014] Furthermore, in step S1, the molar ratio of the strong base to the boron nitride BN is 3:1-2.

[0015] Furthermore, the mixture in step S1 is transferred to a reactor after mixing, and the reactor is sealed and kept at 180° C. for 3 hours. After the reaction in the reactor is completed, the reactor is cooled to room temperature, and the concentration of the BN dispersion is 0.95 mg / mL by ultrasonic centrifugation.

[0016] Furthermore, in step S4, DTPMPA-Cu 2+ The chelation ratio is 16:1.

[0017] Further, in terms of mass percentage, the BN-DTPMPA-Cu 2+ The filler accounts for the PET / BN-DTPMPA-Cu 2+ Composite thermal conductive insulation flame retardant thermal interface material 1% -25%.

[0018] Furthermore, the composite thermally conductive insulating flame-retardant thermal interface material in step S6 is prepared by co-extrusion at a temperature between 20° C. and 300° C., for 5 min to 12 h, and at a pressure of 1 MPa to 30 MPa, preferably 15 MPa.

[0019] Furthermore, the thermally conductive, insulating, flame-retardant thermal interface material comprises a resin matrix, a flame-retardant material and a thermally conductive filler BN (boron nitride nanosheets are thermally conductive fillers), wherein the resin matrix is ​​PET (polyethylene terephthalate); and the flame-retardant material is DTPMPA (diethylenetriaminepentamethylenephosphonic acid).

[0020] In some embodiments of the present invention, the resin matrix can be one or more of polyethylene, polypropylene, polyvinyl chloride, polylactic acid (PLA), thermoplastic polyurethane elastomer rubber (TPU), ethylene-vinyl acetate copolymer (EVA), polyethylene terephthalate (PET), polyphenylene sulfide (PPS) and nylon (NYLON); the preferred resin is polyethylene terephthalate (PET).

[0021] In some embodiments of the present invention, the flame retardant includes antimony trioxide, melamine cyanurate, tribromophenol, aluminum tripolyphosphate, tetrabromobisphenol A, pentabromotoluene, hexabromocyclododecane, ammonium polyphosphate, stannous zincate, aluminum hydroxide, magnesium hydroxide, and chlorinated polyethylene. However, it is easy to pollute the environment during use, so the above-mentioned new flame retardants include boron nitrogen intumescent flame retardants, multifunctional organic-inorganic hybrid flame retardants, phosphorus-nitrogen cage-type silsesquioxane flame retardants, phosphorus-nitrogen intumescent flame retardants, and graphene-based hybrid flame retardants; preferably phosphorus-nitrogen intumescent flame retardants and boron nitrogen intumescent flame retardants.

[0022] In some embodiments of the present invention, the chelating agent mainly utilizes multiple lone electron pairs of atoms such as O, N, S, and P to combine with the outer empty orbitals of transition metal ions to form ligands, which are then precipitated; they mainly include polyethyleneimine (PEI), sulfonated poly (carboxylic acid) (SPCA), diethylenetriaminepentamethylenephosphonic acid (DTPMPA), phosphinopolycarboxylic acid (PPCA), catechol, etc.; the preferred chelating agent is diethylenetriaminepentamethylenephosphonic acid (DTPMPA).

[0023] In some embodiments of the present invention, the transition metal ion includes one or more of Cr3+, Mn2+, Fe3+, Co2+, Ni2+, Cu2+, Zn2+, etc.; preferably, the transition metal ion is Cu2+.

[0024] In some embodiments of the present invention, the two-dimensional layered material includes one or more of graphene, boron nitride, MXene, transition metal chalcogenides, and black phosphorene; preferably, the two-dimensional layered material is boron nitride.

[0025] In some embodiments of the present invention, the solvent used includes: one or more of ethanol, isopropanol, N-methylpyrrolidone, N,N-dimethylformamide, dimethyl sulfoxide, distilled water, tetrahydrofuran, chloroform, dichloromethane, ether, acetone and diacetone alcohol; preferably, the mixed solvent is ethanol, isopropanol and N-methylpyrrolidone.

[0026] The composite thermally conductive, insulating, flame-retardant thermal interface material is prepared by the above preparation method.

[0027] Compared with the prior art, the technical effects created by the present invention are embodied in:

[0028] (1) The present invention is based on the fact that existing flame retardants have poor environmental protection, low flame retardant efficiency in the resin matrix, large amount of filler added, poor heat dissipation, and heat accumulation during use, which can lead to functional failure, deformation, shortened service life and fire of the device. Therefore, the present invention adopts a new phosphorus flame retardant: diethylenetriaminepentamethylenephosphonic acid (DTPMPA) to adsorb transition metal ions Cu 2+ Catalytic flame retardant, while BN as a thermal conductive filler, due to its unique structure, together with the protective carbon layer similar to the graphene structure, forms a dense protective layer, which blocks oxygen and achieves efficient and excellent flame retardant, which can make the composite material have good fire retardant and thermal conductivity. On the other hand, the hydroxyl groups on the surface of DTPMPA and the stripped BN can make the composite material have good mechanical properties and low interface thermal resistance through non-covalent forces, which promotes the composite material to improve thermal conductivity performance.

[0029] (2) The present invention provides a PET / BN-DTPMPA-Cu 2+ Composite thermally conductive insulating flame retardant thermal interface material, the composite thermally conductive insulating thermal interface material is composed of BN-DTPMPA-Cu 2+ The filler and polyethylene terephthalate (PET) were obtained by blending, extruding, film forming and pressing. 2+ The filler content is 1-25%. The composite thermal conductive insulation flame retardant thermal interface material has good application prospects in the heat dissipation fields of electronic devices, LEDs, etc. 2+ Composite thermally conductive, insulating and flame-retardant thermal interface materials are environmentally friendly and easy to prepare, which greatly improves the safety and wide application of polymer materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a scanning electron microscope (SEM) image of BN peeled off in Example 1 of the present invention;

[0031] Figure 2 DTPMPA-Cu in Example 1 of the present invention 2+UV spectrophotometer curve of chelate DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further defined below in conjunction with specific implementation methods, but the scope of protection required is not limited to the description.

[0033] In the following examples, unless otherwise specified, all raw materials are purchased from commercial sources or prepared by conventional methods in the art. Boron nitride was purchased from Nanjing Xianfeng Nanomaterials Co., Ltd.; polyethylene terephthalate (PET) was purchased from DuPont, USA, brand RE5264; Teflon stainless steel autoclave was from Guangdong Hongchen Instrument Factory, model XS20170918; diethylenetriamine penta methylenephosphonic acid (DTPMPA) was purchased from Shandong Yousuo Chemical Co., Ltd.

[0034] Example 1

[0035] This example provides a PET / BN-DTPMPA-Cu 2+ A method for preparing a composite thermally conductive, insulating, flame-retardant thermal interface material, the method comprising:

[0036] (1) Exfoliation of BN nanosheets

[0037] In a typical experiment, 2.84 g NaOH and 1.08 g KOH were first mixed, and then 75 mL deionized water was added to dissolve. Then, 1 g of block BN powder (white powder, particle size of 1 μm) was placed in the above solution and stirred for 1 h, and the suspension was transferred to a stainless steel autoclave lined with PTFE and then placed in a rotary oven at a speed of 20 rpm / min. The hydrothermal treatment was carried out at 180 ° C for 2 h. After completion, the hydrothermally treated liquid was placed in an ultrasonic treatment for 30 min. Finally, the obtained suspension was centrifuged at 3000 rpm for 10 min to remove large-sized BN particles. The supernatant was washed with deionized water until the pH value of the filtrate reached 6.

[0038] (2) BN-DTPMPA-Cu 2+ Preparation of composite materials

[0039] First, prepare 21 μmol / L diethylenetriaminepentamethylenephosphonic acid (DTPMPA), use a pipette to transfer copper ions of different concentrations, and use a UV spectrophotometer for qualitative calibration. The scanning curve has a maximum peak position at 303 nm, and the optimal DTPMPA-Cu chelation ratio is 16:1. Transfer a certain amount of DTPMPA-Cu 2+ The chelate was mixed with 0.95 mg / mL BN supernatant and stirred for 48 h, and then freeze-dried for 16 h to obtain a white solid, which was BN-DTPMPA-Cu 2+ Composite materials.

[0040] (3) PET / BN-DTPMPA-Cu 2+ Preparation of composite materials

[0041] Polyethylene terephthalate (PET) and BN-DTPMPA-Cu 2+ The composite materials were blended and stirred evenly, with a mass ratio of 19:1. In terms of mass percentage, BN-DTPMPA-Cu 2+ The amount of the composite material added was 5% of the amount of polyethylene terephthalate (PET). 2+ The composite material was prepared by blending and extruding at a temperature of 100°C, a time of 6 hours, and a pressure of 15 MPa to obtain PET / BN-DTPMPA-Cu 2+ Composite thermal conductive insulation flame retardant thermal interface material PET@5%BN-DTPMPA-Cu 2+ .

[0042] Example 2

[0043] This example provides a PET / BN-DTPMPA-Cu 2+ A method for preparing a composite thermally conductive, insulating, flame-retardant thermal interface material, the method comprising:

[0044] (1) Exfoliation of BN nanosheets

[0045] In a typical experiment, 2.84 g NaOH and 1.08 g KOH were first mixed, and then 75 mL deionized water was added to dissolve. Then, 1 g of block BN powder (white powder, particle size of 1 μm) was placed in the above solution and stirred for 1 h, and the suspension was transferred to a stainless steel autoclave lined with PTFE and then placed in a rotary oven at a speed of 20 rpm / min. The hydrothermal treatment was carried out at 180 ° C for 2 h. After completion, the hydrothermally treated liquid was placed in an ultrasonic treatment for 30 min. Finally, the obtained suspension was centrifuged at 3000 rpm for 10 min to remove large-sized BN particles. The supernatant was washed with deionized water until the pH value of the filtrate reached 6.

[0046] (2) BN-DTPMPA-Cu 2+ Preparation of composite materials

[0047] First, 21 μmol / L diethylenetriaminepentamethylenephosphonic acid (DTPMPA) was prepared, and copper ions of different concentrations were transferred with a pipette. The UV spectrophotometer was used for qualitative calibration. The scanning curve had a maximum peak position at 303 nm. DTPMPA-Cu 2+ The optimal chelation ratio is 16:1. Take a certain amount of DTPMPA-Cu2+ The chelate was mixed with 0.95 mg / mL BN supernatant and stirred for 48 h, and then freeze-dried for 16 h to obtain a white solid, which was BN-DTPMPA-Cu 2+ Composite materials.

[0048] (3) PET / BN-DTPMPA-Cu 2+ Preparation of composite materials

[0049] Polyethylene terephthalate (PET) and BN-DTPMPA-Cu 2+ The composite materials were blended and stirred evenly, with a mass ratio of 9:1. In terms of mass percentage, BN-DTPMPA-Cu 2+ The amount of filler added was 10% of the amount of polyethylene terephthalate (PET). 2+ The composite material was prepared by blending and extruding at a temperature of 100°C, a time of 6 hours, and a pressure of 15 MPa to obtain PET / BN-DTPMPA-Cu 2+ Composite thermal conductive insulation flame retardant thermal interface material PET / 10% BN-DTPMPA-Cu 2+ .

[0050] Example 3

[0051] This example provides a PET / BN-DTPMPA-Cu 2+ A method for preparing a composite thermally conductive, insulating, flame-retardant thermal interface material, the method comprising:

[0052] (1) Exfoliation of BN nanosheets

[0053] In a typical experiment, 2.84 g NaOH and 1.08 g KOH were first mixed, and then 75 mL deionized water was added to dissolve. Then, 1 g of block BN powder (white powder, particle size of 1 μm) was placed in the above solution and stirred for 1 h, and the suspension was transferred to a stainless steel autoclave lined with PTFE and then placed in a rotary oven at a speed of 20 rpm / min. The hydrothermal treatment was carried out at 180 ° C for 2 h. After completion, the hydrothermally treated liquid was placed in an ultrasonic treatment for 30 min. Finally, the obtained suspension was centrifuged at 3000 rpm for 10 min to remove large-sized BN particles. The supernatant was washed with deionized water until the pH value of the filtrate reached 6.

[0054] (2) BN-DTPMPA-Cu 2+ Preparation of composite materials

[0055] First, 21 μmol / L diethylenetriaminepentamethylenephosphonic acid (DTPMPA) was prepared, and copper ions of different concentrations were transferred with a pipette. The UV spectrophotometer was used for qualitative calibration. The scanning curve had a maximum peak position at 303 nm. DTPMPA-Cu 2+ The optimal chelation ratio is 16:1. Take a certain amount of DTPMPA-Cu 2+ The chelate was mixed with 0.95 mg / mL BN supernatant and stirred for 48 h, and then freeze-dried for 16 h to obtain a white solid, which was BN-DTPMPA-Cu 2+ Composite materials.

[0056] (3) PET / BN-DTPMPA-Cu 2+ Preparation of composite materials

[0057] Polyethylene terephthalate (PET) and BN-DTPMPA-Cu 2+ The composite materials were blended and stirred evenly, with a mass ratio of 17:3. In terms of mass percentage, BN-DTPMPA-Cu 2+ The amount of filler added was 15% of the amount of polyethylene terephthalate (PET). 2+ The composite material was prepared by blending and extruding at a temperature of 100°C, a time of 6 hours, and a pressure of 15 MPa to obtain PET / BN-DTPMPA-Cu 2+ Composite thermal conductive insulation flame retardant thermal interface material PET / 15% BN-DTPMPA-Cu 2+ .

[0058] Example 4

[0059] This example provides a method for preparing a composite thermally conductive, insulating, flame-retardant thermal interface material, the preparation method comprising:

[0060] (1) Exfoliation of BN nanosheets

[0061] In a typical experiment, 2.84 g NaOH and 1.08 g KOH were first mixed, and then 75 mL deionized water was added to dissolve. Then, 1 g of block BN powder (white powder, particle size of 1 μm) was placed in the above solution and stirred for 1 h, and the suspension was transferred to a stainless steel autoclave lined with PTFE and then placed in a rotary oven at a speed of 20 rpm / min. The hydrothermal treatment was carried out at 180 ° C for 2 h. After completion, the hydrothermally treated liquid was placed in an ultrasonic treatment for 30 min. Finally, the obtained suspension was centrifuged at 3000 rpm for 10 min to remove large-sized BN particles. The supernatant was washed with deionized water until the pH value of the filtrate reached 6.

[0062] (2) BN-DTPMPA-Cu 2+ Preparation of composite materials

[0063] First, 21 μmol / L diethylenetriaminepentamethylenephosphonic acid (DTPMPA) was prepared, and copper ions of different concentrations were transferred with a pipette. The UV spectrophotometer was used for qualitative calibration. The scanning curve had a maximum peak position at 303 nm. DTPMPA-Cu 2+ The optimal chelation ratio is 16:1. Take a certain amount of DTPMPA-Cu 2+ The chelate was mixed with 0.95 mg / mL BN supernatant and stirred for 48 h, and then freeze-dried for 16 h to obtain a white solid, which was BN-DTPMPA-Cu 2+ Composite materials.

[0064] (3) PET / BN-DTPMPA-Cu 2+ Preparation of composite materials

[0065] Polyethylene terephthalate (PET) and BN-DTPMPA-Cu 2+ The composite materials were blended and stirred evenly, with a mass ratio of 4:1. In terms of mass percentage, BN-DTPMPA-Cu 2+ The amount of filler added was 20% of the amount of polyethylene terephthalate (PET). 2+ The composite material was prepared by blending and extruding at a temperature of 100°C, a time of 6 hours, and a pressure of 15 MPa to obtain PET / BN-DTPMPA-Cu 2+ Composite thermal conductive insulation flame retardant thermal interface material can be referred to as PET / 20% BN-DTPMPA-Cu 2+ .

[0066] Comparative Example 1

[0067] The performance test of pure polyethylene terephthalate (PET) is shown in Table 1.

[0068] Comparative Example 2

[0069] The same preparation steps as those in Example 1 (1) were used. The peeled BN supernatant was vacuum dried for 12 hours to obtain a white solid powder, which was then co-extruded with polyethylene terephthalate (PET), wherein the amount of BN powder added accounted for 20% of the amount of polyethylene terephthalate (PET) added, in terms of mass percentage. Therefore, the PET / BN composite thermal conductive flame-retardant interface material prepared in this comparative example can be referred to as PET / 20%BN.

[0070] Comparative Example 3

[0071] The BN in all steps of Example 1 was replaced with GO, and the other steps were the same, and then it was mixed with polyethylene terephthalate (PET) by extrusion, wherein the amount of GO powder added accounted for 20% of the amount of polyethylene terephthalate (PET) added by mass percentage. Therefore, the PET / GO composite thermal conductive flame retardant interface material prepared in this comparative example can be referred to as PET / 20% GO.

[0072] Comparative Example 4

[0073] In Example 1, BN in all steps was replaced by GO, and the remaining steps were the same. Polyethylene terephthalate (PET) and GO-DTPMPA-Cu 2+ The composite materials were blended and stirred evenly, with a mass ratio of 19:1. In terms of mass percentage, GO-DTPMPA-Cu 2+ The amount of the composite material added was 5% of the amount of polyethylene terephthalate (PET). 2+ The composite material was prepared by blending and extruding at a temperature of 100°C, a time of 6 h, and a pressure of 15 MPa to obtain PET / GO-DTPMPA-Cu 2+ Composite thermal conductive insulation flame retardant thermal interface material PET / 5% GO-DTPMPA-Cu 2+ .

[0074] The products prepared in Examples 1-4 and Comparative Examples 1-4 were respectively selected to conduct thermal conductivity, limited oxygen index, cone calorimeter and other tests. The test results are shown in Table 1:

[0075]

[0076] Table 1 Summary of the performance tests of the composite materials of Examples 1-4 and Comparative Examples 1-4 Table 1 shows that BN was firstly stripped using a strong base, and then BN-DTPMPA-Cu 2+ PET / BN-DTPMPA-Cu was prepared by co-extrusion of filler and polyethylene terephthalate (PET). 2+ Composite thermal conductive insulation flame retardant thermal interface material. In the embodiment, polyethylene terephthalate (PET) is mixed with BN-DTPMPA-Cu 2+ The increase of filler content makes PET / BN-DTPMPA-Cu 2+ The thermal conductivity of the composite material is greatly improved, reaching 0.60W m -1 k -1 Compared with pure polyethylene terephthalate, it is increased by 300%. In the examples, 5%, 10%, 15%, and 20% BN-DTPMPA-Cu are added respectively. 2+After filling, the LOI value is greatly improved to 31.2%, PET / 20% BN-DTPMPA-Cu 2+ The LOI value is much higher than that of PET / 5%GO-DTPMPA-Cu 2+ .

[0077] PET / BN-DTPMPA-Cu 2+ The composite material has good flame retardant properties. Pure polyethylene terephthalate (PET) shows a shorter ignition time of 105s and a peak heat release rate of 1340Kw / m at 220s. 2 , PET / 20%BN-DTPMPA-Cu 2+ The composite material showed a significant extension time of 120s, and the peak heat release rate reached 840Kw / m at 450s. 2 , which is 37% less than that of pure polyethylene terephthalate (PET). In addition, due to the shielding effect of BN nanosheets and the catalytic carbonization of Cu, PET / 20%BN-DTPMPA-Cu 2+ The composite material exhibited excellent smoke suppression capability with a smoke production rate (SPR) of 0.31m 2 / s, which is significantly lower than that of pure polyethylene terephthalate (PET) by 57%. It is worth noting that PET / 20% BN-DTPMPA-Cu 2+ The composite material produced the lowest COP (0.0054 g / s) during the entire combustion process, indicating that it has excellent smoke suppression effect. The combustion growth rate index of pure polyethylene terephthalate (PET) is 6.09. The material is very easy to burn, and the higher the fire hazard factor; PET / 20% BN-DTPMPA-Cu 2+ The combustion growth rate index of the composite material is 3.43, which reduces the fire intensity. 2+ The addition of makes PET have good flame retardant properties. In summary, the present invention enhances the thermal conductivity and flame retardant properties of polyethylene terephthalate through non-covalent functionalization.

[0078] Finally, it should be pointed out that the above embodiments are only representative examples of the present invention. Obviously, the technical solution of the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by ordinary technicians in this field should be considered as the protection scope of the present invention.

Claims

1. A method for preparing a composite thermally conductive, insulating, flame-retardant thermal interface material, characterized in that: The steps include: S1: placing a strong base and boron nitride BN powder into a stainless steel reactor, and causing a hydrothermal reaction in a closed environment with a pressure of more than 10 MPa and in water; S2: subjecting the solution obtained in step S1 to ultrasonic centrifugation until it becomes neutral and collecting the boron nitride BN supernatant; S3: prepare 21 μmol / L diethylenetriaminepentamethylenephosphonic acid DTPMPA; S4: prepare 10-150 μmol / L anhydrous copper sulfate solution; S5: DTPMPA was added to Cu 2+ Chelation was performed to obtain DTPMPA-Cu 2+ , measure a certain amount of DTPMPA-Cu 2+ Stir with boron nitride BN supernatant for 48 hours and then vacuum dry; S6: The filler dried in step S5 is mixed with polyethylene terephthalate (PET) in a certain proportion, and PET / BN-DTPMPA-Cu is prepared by co-extrusion. 2+ Composite thermally conductive, insulating and flame-retardant thermal interface material.

2. The preparation method according to claim 1, characterized in that: In step S1, the strong base is potassium hydroxide or sodium hydroxide, and the mass ratio of the strong base is 1:2-3.

3. The preparation method according to claim 1, characterized in that: In step S1, the molar ratio of the strong base to the boron nitride BN is 3:1-2.

4. The preparation method according to claim 1, characterized in that: In the step S1, the mixture is mixed and transferred to a reactor, and the reactor is sealed and kept in a heating environment at 180° C. for 3 hours.

5. The preparation method according to claim 4, characterized in that: After the reaction in the reactor is finished, the reactor is cooled to room temperature, and the concentration of the BN dispersion liquid stripped by ultrasonic centrifugation is 0.95 mg / mL.

6. The preparation method according to claim 1, characterized in that: In step S4, DTPMPA-Cu 2+ The chelation ratio is 16:

1.

7. The preparation method according to claim 1, characterized in that: In terms of mass percentage, the BN-DTPMPA-Cu 2+ The filler accounts for the PET / BN-DTPMPA-Cu 2+ Composite thermal conductive insulation flame retardant thermal interface material 1%-25%.

8. The preparation method according to claim 1, characterized in that: The composite thermally conductive, insulating, flame-retardant thermal interface material in step S6 is prepared by co-mixing and extrusion at a temperature between 20° C. and 300° C., a time of 5 min to 12 h, and a pressure of 1 MPa to 30 MPa.

9. The preparation method according to claim 1, characterized in that: The thermally conductive, insulating and flame-retardant thermal interface material comprises a resin matrix, a flame-retardant material and the thermally conductive filler BN described in claim 5, wherein the resin matrix is ​​PET (polyethylene terephthalate); and the flame-retardant material is DTPMPA (diethylenetriaminepentamethylenephosphonic acid).

10. A composite thermally conductive, insulating, flame-retardant thermal interface material prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Boron nitride composite high-thermal-conductivity insulating polymer composite material and preparation method thereof

    CN110951254A

  • Phosphorus-nitrogen-containing carboxylic acid compound, modified boron nitride nanosheet and flame-retardant heat-conducting epoxy resin composite material as well as preparation method and application thereof

    CN117924368A

  • Preparation method and application of high-thermal-conductivity SiO2-coated BNNS composite filler

    CN118725772A

Cited By

  • A highly thermally conductive adhesive lipoic acid-based thermal interface material, method of manufacture and use

    CN122542001A